Visual evoked potential-based acuity assessment in normal vision, artificially degraded vision, and in patients. Issue 3 (26th February 2008) - Bach, M; Maurer, J P; Wolf, M E
Abstract : Aims: To assess visual acuity (VA) objectively using visual evoked potentials (VEPs), avoiding subjective trace evaluation and providing an acuity estimate with associated confidence limits. Methods: 40 normal subjects and 24 patients (with corneal and retinal diseases, decimal VA range 0.15–1.1 ( = 0.8logMAR to −0.04logMAR )) participated in the study. Checkerboard stimuli with six check sizes covering 0.05–0.4° (or 0.09–0.8° for visual acuities below 0.35 ( = 0.46logMAR ) were presented in brief-onset mode (40 ms on, 93 ms off) at 7.5 Hz. In normal subjects, the stimuli were also optically degraded by frosted occluders resulting in a decimal VA range of 0.13–2.8 ( = 0.9logMAR to −0.45logMAR ). Altogether, 108 steady-state VEPs were recorded with a Laplacian montage (2×Oz−(RO+LO)). Fourier analysis yielded the magnitude (A) at the stimulus frequency, and the average of the two neighboring frequencies as noise estimate (N). A and N determine the significance level p of the response, and from their ratio the non-noise-contaminated response (A*) can be calculated. Tuning curves were obtained by plotting A* vs the dominant spatial frequency of the corresponding checkerboard. A fully automatic algorithm used the significance level (p<5%) and A* to automatically select an appropriate region in the high spatial-frequency range on which a linear regression was performed, yielding a zero-amplitude extrapolated spatial frequency SF0 . Subjective VA was obtained with the automated "Freiburg Acuity Test". Results: The brief-onset presentation evoked high VEP amplitudes; however, many tuning curves displayed the well-known "notch" at intermediate check sizes. The fully automated analysis algorithm succeeded in 107 of 108 cases and effectively ignored the notch, if present. The relation between logVA and log(SF0 ) was a constant factor throughout the range tested: logVA = log(SF0 )/17.6 cpd. In more than 95% of all cases, the acuity predicted from SF0 coincided within a factor of two (up and down, or ±0.3 logMAR) with subjective VA with a coefficient of correlation of 0.90. Conclusion: The fully automated analysis avoided subjective problems in peak-trough assessment. The results provide quantitative limits to assess patients with possible malingering.